On the Value of Action and Participatory Research for Intercultural Theology: Reflections in the Light of a Research Project on “Science and Religion in French-Speaking Africa” - Toren, Bernard van den (Mission studies, 2018)
This article explores the importance of “action research” and “participatory research” (ar and pr) for intercultural theology. After introducing these research strategies, it provides a theological rationale for their use in intercultural theology: (1) they move beyond false dichotomies between theoretical and practical theology; (2) they understand professional theologians as part of communities of believers; and (3) they allow for intercultural encounters which approach “the other” as partners in research rather than merely objects of research. Using the example of a research project which studies attitudes to the interface between science and Christian faith among African university students and academics, the article considers three crucial issues for the value and use of ar and pr in intercultural theology: (1) the intrinsic motivation of the partners for intercultural research projects, (2) the role of shared visions of change and (3) the question of truth implied in visions of human flourishing.1